2017
DOI: 10.1371/journal.pone.0186221
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing of orientation discrimination in anisometropic amblyopia

Abstract: Cognition is very important in our daily life. However, amblyopia has abnormal visual cognition. Physiological changes of the brain during processes of cognition could be reflected with ERPs. So the purpose of this study was to investigate the speed and the capacity of resource allocation in visual cognitive processing in orientation discrimination task during monocular and binocular viewing conditions of amblyopia and normal control as well as the corresponding eyes of the two groups with ERPs. We also sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(77 reference statements)
0
4
0
2
Order By: Relevance
“…The AE showed a significantly longer RT than the NE(DE), which is consistent with previous works involving psychophysics 85 – 87 or EEG measurement. 88 The temporal response curve had a flat region that followed the hump, where the stimulus had no influence on the response (see Fig. 6 a, Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The AE showed a significantly longer RT than the NE(DE), which is consistent with previous works involving psychophysics 85 – 87 or EEG measurement. 88 The temporal response curve had a flat region that followed the hump, where the stimulus had no influence on the response (see Fig. 6 a, Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Wang has concluded that both the amblyopic eye and fellow eye exhibiting the longer latency of P3b components as well as the larger amplitude of novelty P300 and P3b. The above researches demonstrate abnormal neural responses of the amblyopic eye at the middle and late stages of cognitive processing, indicating that the amblyopic eye needs to take more time or integrate more resources to process the same visual task [85].…”
Section: Amblyopia and Managementmentioning
confidence: 98%
“…Desde el punto de vista de la percepción, la mayoría de los autores concuerda con que la ambliopía se da cuando hay una discordancia entre los estímulos percibidos por cada ojo (10). Aún se mantienen reminicencias de la primitiva definición de Von Graefe, pues en la consulta clínica optométrica no se suelen apreciar causas o alteraciones físicas (11)(12)(13), y pocas veces se toma en cuenta el nivel de sensibilidad al contraste, lo cual ha demostrado también que se ve alterado (4). A esto se le suele agregar que la habilitación visual mediante los métodos ópticos tradicionales resulta insuficiente (14), pero que con procedimientos terapéuticos adecuados, como el parchado, la penalización o el aprendizaje visuoperceptual puede ser reversible (3).…”
Section: Factores Causalesunclassified
“…Se acepta, cada vez más, que este trastorno afecta los procesos perceptuales y multisensoriales de alto nivel (21). Es decir, aunque no sean obvias las causas orgánicas, se entiende que el neurodesarrollo y la neuroestructura se ven alteradas (22). Los circuitos neuronales se encuentran distorsionados (23), e incluso esto se toma como uno de los procesos que dan inicio a la ambliopía, la inhibición de las vías visuales del ojo ambliope por parte del ojo dominante, con la consecuente alteración del cuerpo geniculado lateral (CGL) y de la corteza occipital (24).…”
Section: Factores Causalesunclassified